A gazdaság fehérítése: büntetés és ösztözés:költségek és hasznok egy modellszámítás tükrében - Anikó Bíró; János Vincze (Hungarian Academy of Sciences, Institute of Economics, 2008)
– It is well known that the size of the informal (black or grey) economy causes serious fiscal problems for Hungary. This study makes an attempt to quantify the budgetary and macroeconomic effects of different ways of widening the formal sector (whitening”) with the help of a model. It turns out that if only negative incentives were involved (better enforcement scenario) the real effects would be painful: reduced disposable income and higher labor costs would result in lower consumption, exports, and, a fortiori, GDP growth. Obviously, unemployment would increase, and. less obviously, inflation would pick up. The tradeoff between the reduction of public debt and macroeconomic equilibrium seems to be quantitatively unfavourable. The major alternative policy option is a positive incentives scenario. The simplest measure consists of a substantial reduction in the comparatively large social security contribution rate. Its positive real effects (lower wage costs would lead to higher export growth, GDP and consumption) appear slowly, but after the second year their size would be apprehensible. However, the negative impact on the budget deficit is immediate, and though the real effects would turn the tide eventually, the initial public debt increase would worsen public indebtedness significantly within 2 years. Running scenarios under several behavioral” assumptions, but fixing the current structure of the government finances, we could not find any possibility to simultaneously improve macroeconomic performance and reduce public debt by using the social security contribution rate as the chief vehicle of reform. Combining the incentive scenario with improved enforcement (principally by raising the effective VAT rate) would ameliorate the situation as higher export growth would still be the decisive factor for GDP. On the other hand in this version higher inflation would constitute the main policy concern. Combining incentives with a cut in government investment spending is not necessarily alluring: it would require a very large reduction to undo the negative budgetary impact, while its negative demand effect would also undo the positive effects on GDP and consumption. To summarize: better enforcement alone would be a socially counterproductive way to reduce government debt. The incentive scenario would work out well in the long term, but it would certainly create short term budgetary, and therefore, longer term debt problems. To avoid this it must be combined with better enforcement and, possibly, with a significant expenditure cut.
Keywords: E17; E62; E65; 330; informal economy; tax incentives; quantitative macroeconomic modelling; Schattenwirtschaft; Informelle Wirtschaft; Anreiz; Wirkungsanalyse; Ungarn